Bird : the life and music of Charlie Parker - Haddix, Chuck (Music in American life., 2013)
Saxophone virtuoso Charlie Bird Parker began playing professionally in his early teens, became a heroin addict at 16, changed the course of music, and then died when only 34 years old. This biography weaves together firsthand accounts from those who knew him with new information about his life and career to create a narrative portrait of a tragic genius.